Pedagogical profile of a pupil: occurence vs phenomenon - Mikhno, Oleksandr (Filosofiya osvity. Philosophy of Education, 2019)
Based on the analysis and comparison of the concepts «occurrence» and «phenomenon» in philosophy and pedagogy, the pedagogical profile is substantiated as a phenomenon that differs from occurrence by comprehension, analysis, generalizations, and conclusions. It has been substantiated that the phenomenon in pedagogy is an occurrence that: 1) has its own history, 2) is clearly defined, and 3) its existence has an impact on the subjects of the pedagogical process and the development of pedagogical science. It has been proved that the problem of pedagogical characteristics was developed by the leading domestic educators and psychologists of the middle of the XIX — the second half of the XX century. It has been emphasized that the pedagogical profile has been used in the educational process since the beginning of the twentieth century. It has been concluded that, like every scientific pedagogical phenomenon, the pedagogical profile is subject to operationalization and a holistic study with the definition of the subject, object, chronological boundaries, carrying out of the historic and graphical search, coverage of the contribution of scientists — teachers and psychologists — in its development, a comprehensive analysis of the structure, content and the use of characteristics in educational institutions in different historical periods. The author’s definition of pedagogical profiles as a phenomenon that appeared in the second half of the nineteenth century and was further developed theoretically and methodically by teachers and psychologists O. Lazursky, S. Rubinstein, B. Baev, V. Sukhomlinsky, and others; it is a kind of text in which the value judgments about a pupil are substantiated; it has a structure of the text-reasoning, in which the traits of character and the personality of the pupil are indicated, the arguments are concrete facts of life, the behavior of the pupil, obtained as a result of a long systematic study of the pupil through observation and special research, and the conclusion — pedagogical recommendations, advice on further work with the pupil.